Analysis of different laboratory-scale techniques for preventing coal spontaneous combustion - Theodora Noely Tambaria; Yuichi Sugai; Takehiro Esaki (Cleaner Chemical Engineering, 2024)
The focus of this study is to investigate laboratory-scale techniques aimed at preventing an increase in heat flux, which can potentially lead to spontaneous coal combustion. This research involves two pieces of equipment designed to analyze the heat flux on untreated coal and coal treated with polyvinyl alcohol (PVA). The laboratory equipment consists of a copper cell capable of holding up to 75 ml of coal samples and an aluminum cell designed to accommodate up to 3.17 ml of coal samples. The results on untreated coal showed that copper cell had a higher heat flux and took longer to reach the heat flux peak than aluminum cell. The aluminum cell provided more excellent stability, resulting in consistent heat distribution and dependable outcomes. The analysis using copper and aluminum cells on coal treated with PVA indicates that PVA can effectively reduce the heat of combustion by 35 %. This finding could have significant implications for future coal combustion studies. This study provides valuable insights for future research into coal spontaneous combustion experiments and using PVA to prevent spontaneous coal combustion.